Analytical characterization and pharmacological evaluation of the new psychoactive substance 4‐fluoromethylphenidate (4F‐MPH) and differentiation between the (±)‐threo and (±)‐erythro diastereomers. Issue 3 (7th March 2017) - McLaughlin, Gavin; Morris, Noreen; Kavanagh, Pierce V.; Power, John D.; Dowling, Geraldine; Twamley, Brendan; O'Brien, John; Hessman, Gary; Murphy, Brian; Walther, Donna; Partilla, John S.; Baumann, Michael H.; et al.
Abstract : Misuse of (±)‐ threo ‐methylphenidate (methyl‐2‐phenyl‐2‐(piperidin‐2‐yl)acetate; Ritalin®; MPH) has long been acknowledged, but the appearance of MPH analogs in the form of 'research chemicals' has only emerged in more recent years. 4‐Fluoromethylphenidate (4F‐MPH) is one of these recent examples. This study presents the identification and analytical characterization of two powdered 4F‐MPH products that were obtained from an online vendor in 2015. Interestingly, the products appeared to have originated from two distinct batches given that one product consisted of (±)‐ threo ‐4F‐MPH isomers whereas the second sample consisted of a mixture of (±)‐ threo and (±)‐ erythro 4F‐MPH. Monoamine transporter studies using rat brain synaptosomes revealed that the biological activity of the 4F‐MPH mixture resided with the (±)‐ threo and not the (±)‐ erythro isomers based on higher potencies determined for blockage of dopamine uptake (IC50 4F‐MPHmixture  = 66 nM vs. IC50 (±)‐ threo  = 61 nM vs. IC50 (±)‐ erythro  = 8, 528 nM) and norepinephrine uptake (IC50 4F‐MPHmixture  = 45 nM vs. (±)‐ threo  = 31 nM vs. IC50 (±)‐ erythro  = 3, 779 nM). In comparison, MPH was three times less potent than (±)‐ threo ‐4F‐MPH at the dopamine transporter (IC50  = 131 nM) and around 2.5 times less potent at the norepinephrine transporter (IC50  = 83 nM). Both substances were catecholamine selective with IC50 values of 8, 805 nM and >10, 000 nM for (±)‐ threo ‐4F‐MPH and MPH at the serotonin transporter. These findings suggest that the psychostimulant properties of (±)‐ threo ‐4F‐MPH might be more potent in humans than MPH. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : This study describes the analytical characterization and pharmacological evaluation of two powdered 4‐fluoromethylphenidate (4F‐MPH) products obtained from an Internet retailer. An extensive analysis of this new psychoactive substance suggested the presence of two distinct batches: one product consisted of a diastereomeric (±)‐ threo and (±)‐ erythro mixture whereas the other represented the (±)‐ threo racemate. In vitro transporter assays performed in rat brain synaptosomes demonstrated a catecholamine‐selective uptake inhibition of (±)‐ threo ‐4F‐MPH with little activity at the serotonin transporter. (±)‐ threo ‐4F‐MPH was more potent than methylphenidate.